Worker Protection Standards Regulation Update - Hurner, Laurie (EDIS, 2017)
Article for Citrus Industry Magazine highlighting the EPA Worker Protection Standard Revisions completed in 2015. Article based on information included in the UF/IFAS Private Applicator Agriculture Pest Control manual my Dr. Fred Fishel, Dept of Agronomy and the Edis Document #P1270 "Quick Reference Guide to the Worker Protection Standard (WPS) Revised in 2015.